Former CEO Directors: Lingering CEOs or Valuable Resources? - Fahlenbrach, Rüdiger; Minton, Bernadette A.; Pan, Carrie H. (Review of Financial Studies, 2011)
We investigate corporate governance experts' claim that it is detrimental to a firm to reappoint former CEOs as directors after they step down as CEOs. We find that more successful and more powerful former CEOs are more likely to be reappointed to the board multiple times after they step down as CEOs. Firms benefit, on average, from the presence of former CEOs on their boards. Firms with former CEO directors have better accounting performance, have higher relative turnover-performance sensitivity of the successor CEO, and can rehire their former CEO directors as CEOs after extremely poor firm performance under the successor CEOs.